Efficient synthesis of (S)-2-chloro-1-(2, 4-dichlorophenyl) ethanol using a tetrad mutant alcohol dehydrogenase from Lactobacillus kefir. (October 2019) - Chen, Nan; Chen, Yinyue; Tang, Yunping; Zhao, Qiaoling; Liu, Chenjuan; Niu, Wenwen; Huang, Peiyang; Yu, Fangmiao; Yang, Zuisu; Ding, Guofang
Graphical abstract: Highlights: A mutant alcohol dehydrogenase (ADH) was first used for producing the luliconazole intermediate. The reaction was catalyzed by this mutant ADH with excellent stereoselectivity (ee 99.5%). Using 50 g/L crude enzyme, 60 g/L substrate was completely reduced in 6 h. Abstract: As the key chiral intermediate of luliconazole, (S)-2-chloro-1-(2, 4-dichlorophenyl) ethanol ((S)-CPEO) was prepared from 2-chloro-1-(2, 4-dichlorophenyl) ethanone (CPE) using a tetrad mutant alcohol dehydrogenase (A94T/F147L/L199H/A202L) from Lactobacillus kefir (LK-TADH) coupled with glucose dehydrogenase (GDH). Enzyme-substrate docking simulation was used to reveal the molecular basis of the increases in catalytic ability and enantiomeric excess (ee) values of LK-TADH. Furthermore, using 60 g/L of CPE for gram-scale preparation of (S)-CPEO, the conversion rate reached approximately 100% after 6 h at 35 °C, and the ee value of the final product was 99.5%. Our research provides a foundation for preparing of (S)-CPEO using LK-TADH.